Behaviour in networks of collaborators: theory and evidence from the English judiciary - Leaver, C; Vidal, J (University of Oxford, 2007)
This paper uses data on judicial citations to explore whether the diffusion and/or application of knowledge within an organisation is affected by worker connectivity. Developing a simple model of discretionary citations, we distinguish between two hypotheses: knowledge diffusion whereby connected judges are more likely to be aware of each others' cases than unconnected judges, and socialisation whereby judges are more likely to be positively disposed to judges to whom they are more connected. Our empirical strategy exploits three important institutional features: (a) the random allocation of judges to case committees in the English Court of Appeal, (b) the existence of both positive and neutral citations and (c) the fact that connections occur over time. We are able to reject the knowledge diffusion hypothesis in its simplest form. We are unable to reject the socialisation hypothesis, and find strong evidence to support it. The paper concludes with a discussion of implications for other knowledge-based organisations.